The Minority and the State: Chinese Muslims in the Modern History of Indonesia - Ubaedillah, Achmad (Al-Jami'ah Research Centre, 2023)
Despite their long existence in Nusantara, the Chinese ethnic groups remain less represented or even misrepresented in the history of Indonesia, resulting in negative stereotypes and attitudes towards the community. Sejarah Nasional Indonesia (SNI) and history textbooks for schools and universities, for instance, do not provide adequate narratives about Chinese contributions to Indonesian politics and economy during the pre- and post-independence era. This study aims to critically analyse the representation of Chinese ethnicities in the modern history of Indonesia, more specifically, the SNI and history textbooks for Islamic schools and universities. The findings of the study suggest that there was an unwritten history of Chinese and Chinese Muslims, especially during the Sukarno and Suharto regimes, which then Abdurrahman Wahid began to include. The study recommends new narratives of Chinese Muslims in modern Indonesian history by proposing some notable scholars who extensively worked on the History of Islam in Java, to which Chinese Muslims had contributed. [Kendati sudah berada di Indonesia berabad-abad lamanya, etnis Tionghoa tidak banyak tercatat dalam narasi sejarah Indonesia. Misrepresentasi etnis Tionghoa di Nusantara bahkan menyebabkan adanya stereotip dan sikap negatif terhadap etnis tersebut. Sejarah Nasional Indonesia (SNI) dan buku teks sejarah di sekolah dan universitas, misalnya, tidak banyak menyebutkan kontribusi etnis Tionghoa secara politik maupun ekonomi selama masa pra dan pasca kemerdekaan. Studi ini merupakan analisis kritis terhadap representasi etnis Tionghoa dalam sejarah modern Indonesia, khususnya dalam Sejarah Nasional Indonesia (SNI) dan buku teks sejarah di sekolah dan kampus Islam. Temuan kajian menunjukkan adanya sejarah yang tidak tercatat tentang peran Muslim Tionghoa selama rezim Sukarno dan Suharto, yang kemudian mulai diubah oleh rezim Gus Dur. Studi ini merekomendasikan adanya penulisan ulang sejarah Muslim Tionghoa di Indonesia dengan mengintegrasikan temuan studi beberapa sarjana ternama yang banyak meneliti mengenai Islam di Jawa dan peran etnis Tionghoa di dalamnya.]